Real‑world safety evaluation of tranexamic acid: Signal detection from FAERS and VigiAccess databases - Jing Feng; Chiwei Guo; Shujuan Zhao (PLoS ONE, 2026)
Background Tranexamic acid (TXA) is an antifibrinolytic agent commonly used to mitigate blood loss across various medical indications. Despite its widespread use, comprehensive data on its safety profile remain limited. This study aimed to systematically evaluate adverse events (AEs) associated with TXA. Methods Adverse event reports were extracted from the U.S. Food and Drug Administration’s Adverse Event Reporting System (FAERS) and the VigiAccess databases. Disproportionality analyses were conducted using reporting odds ratio (ROR), proportional reporting ratio (PRR), the Medicines and Healthcare products Regulatory Agency (MHRA) method, Bayesian confidence propagation neural network (BCPNN), and multi-item gamma Poisson shrinker (MGPS). Results A total of 17,787 TXA-related AE reports were identified. A higher proportion of reports involved females, with older adults (≥ 65 years) accounting for the largest proportion in FAERS and younger individuals (18–44 years) in VigiAccess. Overlapping PTs, including seizures, pulmonary embolism and anaphylactic reactions, were identified. Significant differences for TXA-related AEs were found by gender, age and death outcomes. Most AEs occurred within the first month, with an early failure pattern. Conclusion This study provides evidence to weigh risks and benefits of TXA by comprehensive assessment of safety profile for TXA. These findings provide valuable references for future pharmacovigilance research on TXA.